Process Of Building An AI Chatbot Scenario For Teaching Mathematics To High School Students - Giam, Nguyen Minh; Doc, Nguyen Van; Nam, Nguyen Thi Hoai; Thanh, Ngo Tu; Giang, Nguyen Thi Huong (Papanda Publisher, 2023)
This article emphasizes the importance of artificial intelligence (AI) in mathematics education and proposes a process for developing an AI Chatbot to support mathematics learning. The purpose is to create an engaging learning environment, provide a valuable tool for teachers and educators, improve the quality of mathematics education, and enhance mathematical skills effectively through artificial intelligence. The article presents the process of building a script for the Chatbot, including planning, design, deployment, testing, and integration into teaching. It analyzes the application of artificial intelligence and machine learning in general and the role of AI Chatbot in education in particular. The design includes a 5-step process for developing an AI Chatbot for teaching mathematics. It starts with defining the script structure, creating script content, integrating the script into AI Chatbot, testing, and conducting trial lessons, and concludes with an evaluation. This process ensures the systematic and efficient development of the Chatbot. The product of this process is an AI Chatbot with the functionality of a virtual teacher capable of supporting the teaching of mathematics and fostering mathematical thinking in students. Using AI Chatbots in mathematics education has the potential to enhance interaction and learning performance. It not only helps students gain a deeper understanding but also stimulates mathematical thinking and learning motivation.